Can light‐saturated photosynthesis in lowland tropical forests be estimated by one light level?. (14th June 2020) - Verryckt, Lore T.; Ellsworth, David S.; Vicca, Sara; Van Langenhove, Leandro; Peñuelas, Josep; Ciais, Philippe; Posada, Juan M.; Stahl, Clément; Coste, Sabrina; Courtois, Elodie A.; Obersteiner, Michael; Chave, Jérôme; et al.
Abstract: Leaf‐level net photosynthesis ( A n ) estimates and associated photosynthetic parameters are crucial for accurately parameterizing photosynthesis models. For tropical forests, such data are poorly available and collected at variable light conditions. To avoid over‐ or underestimation of modeled photosynthesis, it is critical to know at which photosynthetic photon flux density (PPFD) photosynthesis becomes light‐saturated. We studied the dependence of A n on PPFD in two tropical forests in French Guiana. We estimated the light saturation range, including the lowest PPFD level at which A sat ( A n at light saturation) is reached, as well as the PPFD range at which A sat remained unaltered. The light saturation range was derived from photosynthetic light‐response curves, and within‐canopy and interspecific differences were studied. We observed wide light saturation ranges of A n . Light saturation ranges differed among canopy heights, but a PPFD level of 1, 000 µmol m −2 s −1 was common across all heights, except for pioneer trees species that did not reach light saturation below 2, 000 µmol m −2 s −1 . A light intensity of 1, 000 µmol m −2 s −1 sufficed for measuring A sat of climax species at our study sites, independent of the species or the canopy height. Because of the wide light saturation ranges, results from studies measuring A sat at higher PPFD levels (for upper canopy leaves up to 1, 600 µmol m −2 s −1 ) are comparable with studies measuring at 1, 000 µmol m −2 s −1 .